Correlation Analysis Between Water Discharge and Suspended Load During The Rainy Season in The Downstream Ciliwung River, Jakarta - Rizkah Afifah, Nabilah; Liyantono; Saptomo, Satya Krido (Jurnal Keteknikan Pertanian, 2025)
The Ciliwung River Basin originates at the foot of Mount Pangrango in West Java and flows downstream to Jakarta, with a catchment area of approximately 387 km². The downstream segment in Jakarta is highly vulnerable to sedimentation, which reduces flow capacity, damages infrastructure, and increases flood risk. These conditions highlight the urgency of analyzing the relationship between water discharge and total suspended solid (TSS) load in the downstream Ciliwung River as a scientific basis for river management in Jakarta. This study analyzed the correlation between water discharge and total suspended solids (TSS) in the downstream segment of the basin. Water samples were collected from three observation points, resulting in 11 observations and 33 samples in January 2025. The relationship between water discharge and TSS load was examined using linear regression correlation analysis in order to identify the degree of association and to establish the regression model between both variables. TSS ranged from 8.5 to 284.5 mg/L, while Water discharge varied from 2.55 to 45.47 m³/s. The correlation coefficients were obtained as 0.9721 at the upstream site, 0.9151 at the middle stream site, and 0.0006 at the downstream site. A strong positive correlation was found in the upstream and midstream segments, while the downstream segment showed no significant correlation, likely due to hydrological and tidal effects. These results contribute to a deeper understanding of sediment transport dynamics and can inform sustainable sediment management and dredging strategies in urban river systems.